2016
DOI: 10.1111/jgh.13172
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic factors and trajectory of HRQOL in patients with pancreatic cancer who received psychiatric intervention

Abstract: Early psychiatric intervention in patients with pancreatic cancer may maintain HRQOL. More effective pain management and reduction of psychological distress are important for patients with pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Asides from assessing the evolution of HRQoL in real-life patients receiving first-line chemotherapy, we investigated the prognostic value of baseline HRQoL in our study population. Previous clinical trials and real-life studies have demonstrated that baseline HRQoL and subsequent changes during treatment (global and subscales) are associated with survival of patients with pancreatic cancer[8,9,[11][12][13][14]35]. Our results confirmed this trend in a real-life setting, with patients scoring ≥50 in the QLQ-C30 global health status scale and showing higher OS and PFS.…”
supporting
confidence: 86%
“…Asides from assessing the evolution of HRQoL in real-life patients receiving first-line chemotherapy, we investigated the prognostic value of baseline HRQoL in our study population. Previous clinical trials and real-life studies have demonstrated that baseline HRQoL and subsequent changes during treatment (global and subscales) are associated with survival of patients with pancreatic cancer[8,9,[11][12][13][14]35]. Our results confirmed this trend in a real-life setting, with patients scoring ≥50 in the QLQ-C30 global health status scale and showing higher OS and PFS.…”
supporting
confidence: 86%
“…Reductions in cortisol levels or normalization of diurnal cortisol patterns have also been reported 150,152 . The changes in immunological and endocrine responses associated with psychological interventions do not seem only to exert a beneficial impact on coping strategies, stress relieving, affective symptoms and on quality of life measures [153][154][155] , but there is also some evidence of a long-lasting effect on survival. For instance, in a study with a 11-year follow-up of breast cancer patients, psychological treatment was effective in reducing the risk of recurrence (hazard ratio [HR]= 0.55; 95% CI 0.28-0.93) and death from breast cancer (HR = 0.44; 95% CI 0.32-0.957) 156 .…”
Section: Effects Of Psychological Treatments On Depression In Patientmentioning
confidence: 99%
“…Recent studies have indicated that early psychiatric intervention is essential for patients with cancer and could improve their QoL and prevent subsequent psychological distress. 27,28 Considering the high levels of anxiety about AL-CFR and prolonged treatment in patients with malignant skull base tumors, early psychiatric intervention before surgery is important.…”
Section: Discussionmentioning
confidence: 99%